Investigation of chemical constituents and cytotoxic activity of the lichen Usnea undulata. Issue 1 (26th February 2020) - Tram, Nguyen Thi Thu; Anh, Dinh Hoang; Thuc, Huynh Hoang; Tuan, Nguyen Trong
Abstract: Lichens are a promising source of good anticancer agents. However the study on their bioactivities remains limited, especially in Vietnam. In this study, three extracts of lichen Usnea undulata Stirt. including n ‐hexane, acetone and methanol were investigated for their cytotoxic activity on two human cancer cell lines (MCF‐7, NCI‐H460) and normal fibroblasts by sulforhodamine B (SRB) assay . The results showed that the n‐ hexane extract exhibited the highest inhibition activity with IC50 5.26±0.13 μg/mL for MCF‐7 and 6.83±0.64 μg/mL for NCI‐H460, followed by acetone extract with IC50 66.44±1.37 μg/mL and 92.14±1.49 μg/mL, respectively. The methanol extract possessed weak cytotoxic effect against MCF‐7 and NCI‐H460 (IC50 values more than 100 μg/mL). The n‐ hexane extract demonstrated interesting activity particularly on MCF‐7 as good selectivity index was recorded (SI > 3). The phytochemical study on n‐ hexane and acetone extracts led to the isolation of four compounds including usnic acid (1 ), methyl orsellinate (2 ), methyl β ‐orsellinate (3 ), 7‐hydroxyl‐5‐methoxy‐6‐methylphtalide (4) in which compound (4 ) was isolated the first time in such species. Their structures were elucidated by NMR analysis and compared with literature data.